Ījāz dan Iṭnāb sebagai Strategi Retoris untuk Memperkuat Pesan Ilahi dalam Al-Qur'an - Nur Afni Handayani; Andi Miswar; Mardan (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
The rhetorical excellence of the Qur'an has long been recognized as one of its defining characteristics. However, contemporary Qur'anic scholarship has predominantly emphasized theological, legal, and semantic dimensions, while the communicative functions of classical rhetorical devices remain comparatively underexplored. This study examines ījāz (conciseness) and iṭnāb (elaboration) as rhetorical strategies for reinforcing divine messages in the Qur'an. Employing a qualitative library-based research design, the study applies the analytical framework of classical Arabic balāghah to examine selected Qur'anic verses that exemplify both rhetorical styles. The findings reveal that ījāz reinforces divine messages through linguistic economy, semantic density, and expressive precision, enabling profound meanings to be conveyed with maximum rhetorical impact. Conversely, iṭnāb strengthens divine communication through purposeful elaboration, contextual clarification, persuasive emphasis, and emotional engagement, facilitating deeper cognitive and spiritual internalization of Qur'anic teachings. Rather than representing contrasting rhetorical styles, ījāz and iṭnāb function as complementary communicative strategies whose effectiveness depends on the communicative context and intended persuasive purpose of the discourse. This study contributes to contemporary Qur'anic rhetoric by demonstrating that the persuasive power of the Qur'an emerges not only from the theological content of its messages but also from the strategic deployment of rhetorical forms that optimize meaning, persuasion, and spiritual transformation. These findings extend the study of balāghah beyond stylistic description toward a functional and discourse-oriented understanding of Qur'anic rhetoric.